Tramps in transition: genetic differentiation between populations of an iconic "supertramp" taxon in the Central Indo-Pacific - Ó Marcaigh, Fionn; Marples, Nicola; Kelly, David; Lawless, Naomi; McKeon, Caroline M.; Doyle, Niamh (My University, 2022)
The island monarch ( Monarcha cinerascens) was an original example of the “supertramp strategy ”. This involves well-developed dispersal specialisation, enabling a species to colonise remote islands but leaving it competitively inferior. Supertramps are hypothesised to be excluded from larger islands by superior competitors. It is the only original Melanesian supertramp to occur in Wallacea, home also to the sedentary pale-blue monarch ( Hypothymis puella). We interrogate the supertramp strategy and its biogeographical underpinnings by assessing the population structure of these two monarchs. We sampled island and pale-blue monarchs in Wallacea, collecting DNA and morphological data. We investigated monarch population structure by applying ABGD and Bayesian and Maximum Likelihood methods to their ND2 and ND3 genes. We constructed linear models to investigate the relationships between genetic divergence, dispersal ability, and island area, elevation, and isolation. Wallacea’s deep waters restrict gene flow even in a supertramp, as the Wallacean and Melanesian island monarchs are likely separate species (mean genetic distance: 2.7%). This mirrors the split of the pale-blue monarch from Asia’s black-naped monarch (Hypothymis azurea). We found further population structure within Wallacean and Melanesian island monarch populations. Their genetic divergence was related to elevation, area, and isolation of islands, as well as dispersal ability of birds. However, dispersal ability was independent of island elevation and area. Rather than being r-selected on small, disturbance-prone islands, our results support the view that the island monarch’s supertramp lifestyle is a temporary stage of the taxon cycle, i.e. supertramps may transition into resident species after colonisation. Our models suggest that more dispersive monarchs reach more distant islands, and divergence is promoted on islands that are more distant or larger or more permanent, without selection against dispersal ability per se. We suggest that supertramp lifestyle helps determine the distribution of species across islands, not necessarily the divergence occurring thereafter.
PUBLISHED
Keywords: Dispersal; Island biogeography; Melanesia; Monarchidae; r selection; Speciation; Supertramp strategy; Taxon cycle; Wallacea; BIODIVERSITY; BIOGEOGRAPHY; DISPERSAL RATES; EVOLUTION; Evolutionary Biology; INDONESIA; ISLAND BIOGEOGRAPHY; Ornithology; Sulawesi; cryptic biodiversity; monarch flycatchers; tropical forest biodiversity; wallacea